Thermoexpandable Urethral Nickel–Titanium Stent Memokath for Managing Urethral Bulbar Stricture After Failed Urethroplasty - Martov, Alexey G. (J Endourol Case Rep, 2020)
Introduction: Urethral stenting became popular two decades ago, but nowadays its frequency is slightly decreased because of the rising application of urethroplasty. Today urethral stenting is reserved only for failure after urethral reconstruction or in cases when the plastic surgery is unfavorable. The Memokath stent (Pnn Medical A/S, Kvistgaard, Denmark) is manufactured from a biocompatible alloy of nickel and titanium and known to be the most popular in this field. Case Description: A 38-year-old man with a history of 9 years Memokath urethral stenting was admitted to our clinic with obstructive lower urinary tract symptoms. The indication for Memokath stenting was repeated recurrences after endoscopic and reconstructive operations. The plain radiography showed a normal position of the stent and only the endoscopic examination revealed its total calcification. New superpulse thulium fiber laser has been used to free the stent from the stones and safely remove it without additional urethral injury. Results: The postoperative time was within normal limits, the catheter was removed on the fourth day after operation. Three months follow-up was without stricture recurrence. We continue active surveillance of the patient. Conclusion: The calcification of the stent could be properly diagnosed endoscopically; the Memokath stent could be safely removed in 9 years after implantation; thulium fiber laser is effective and safe in the management of encrusted urethral stent.